The Impact of Total Quality Management on Employee Performance Through Innovative Work Behavior and Dynamic Absorptive Capacity in Salatiga Manufacturing - Carlos; Gede Ariadi (Universitas Negeri Semarang, 2025)
This study examines the relationship between total quality management (TQM) and employee performance by identifying key mediating factors, namely innovative work behaviour and dynamic absorptive capacity. The research investigates how these mediators enhance the effectiveness of TQM in improving employee productivity and performance within manufacturing firms. A research framework was developed and tested using data collected from 114 employees working in manufacturing companies in Salatiga. The data were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The findings reveal that TQM positively influences employee performance, while innovative work behaviour and dynamic absorptive capacity serve as significant mediating variables. Furthermore, both mediators strengthen the relationship between TQM and employee performance. These results suggest that managers should cultivate an innovative work environment by empowering employees to work independently and think creatively. In addition, top management should encourage continuous learning and the application of new knowledge in the workplace to improve operational efficiency and effectiveness.